Psychological consequences of sexual assault - Mason, Fiona; Lodrick, Zoe (Best practice & research. Clinical obstetrics & gynaecology, 2013)
Sexual violence is an important issue worldwide and can have long-lasting and devastating consequences. In this chapter, we outline the psychological reactions to serious sexual assault and rape, including development of post-traumatic stress disorder. Myths and stereotypes surrounding this subject, and their potential effect on the emotional response and legal situation, are discussed.